1992
DOI: 10.3133/pp1506e
|View full text |Cite
|
Sign up to set email alerts
|

Correlation, composition, areal distribution, and thickness of Eocene stratigraphic units, greater Green River basin, Wyoming, Utah, and Colorado

Abstract: The correlation, composition, area! distribution, and thickness of tongues and members of Eocene formations in the greater Green River basin are shown by 11 transbasin stratigraphic correlation diagrams and 15 basin wide isopach maps. The data indicate that the composition and area! distribution of the various stratigraphic units are mostly related to Eocene tectonism and climate changes. Rocks that were deposited in Lake Gosiute in the Green River and Washakie basins in southwest Wyoming are correlated with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 1 publication
0
66
0
Order By: Relevance
“…Lacustrine deposition in the lower LaClede Bed is interrupted by a distinct marker horizon known as the Buff Marker Bed (Roehler, 1973(Roehler, , 1992(Roehler, , 1993. Marked by meter-scale desiccation cracks and a 10-15 m siltstone in the Washakie Basin (Figs.…”
Section: Laney Member Stratigraphymentioning
confidence: 98%
See 1 more Smart Citation
“…Lacustrine deposition in the lower LaClede Bed is interrupted by a distinct marker horizon known as the Buff Marker Bed (Roehler, 1973(Roehler, , 1992(Roehler, , 1993. Marked by meter-scale desiccation cracks and a 10-15 m siltstone in the Washakie Basin (Figs.…”
Section: Laney Member Stratigraphymentioning
confidence: 98%
“…Green River Formation strata are among the most extensively studied in the world, providing a well-constrained stratigraphic and chronological framework (e.g., Bradley, 1929Bradley, , 1964Eugster and Hardie, 1975;Surdam and Wolfbauer, 1975;Stanley, 1979, 1980;Smoot, 1983;Roehler, 1973Roehler, , 1992Roehler, , 1993Carroll and Bohacs, 1999;Smith et al, 2003Smith et al, , 2008. Furthermore, several authors have suggested that changes in regional drainage infl uenced the depositional history of the Green River Formation.…”
Section: Introductionmentioning
confidence: 97%
“…The lacustrine strata of the Green River Formation in the greater Green River Basin is encased in alluvial clastic sedimentary rocks (Bradley, 1964;Roehler, 1992). Alluvial deposits are differentiated into two classes on the basis of petrography: internally sourced quartzo-feldspathic sandstone, assigned to the Wasatch Formation (Denson and Pipiringos, 1969;Braunagel and Stanley, 1977;Sullivan, 1985), and volcaniclastic sandstone (Surdam and Stanley, 1980;Dickinson et al, 1988) that was externally derived from a distant source, assigned to the Bridger, Washakie, and Uinta Formations (Matthew, 1909;Roehler, 1973b;Cashion and Donnell, 1974), as well as the Sand Butte Bed of the Laney Member of the Green River Formation (Roehler, 1973a).…”
Section: Geologic Settingmentioning
confidence: 99%
“…2;Bradley, 1964;Roehler, 1992). Numerous laterally persistent layers of air-fall tuff and sedimentary cyclicity permit a highresolution physical stratigraphy (e.g., Culbertson, 1961;Bradley, 1964;Roehler, 1992).…”
Section: Stratigraphic Contextmentioning
confidence: 99%
“…The single-crystal 40 Ar/ 39 Ar ages reported here are from tuffs 3 and 6 of Culbertson (1961;Fig. 2) from the center of the basin. Tuff 6 is located just below a basin-wide facies transition marking the beginning of maximal expansion of Lake Gosiute (Bradley, 1964;Roehler, 1992) that can be traced into the magnetic polarity sections of Clyde et al (1997Clyde et al ( , 2001P1 and P2 in Figs. 2 and 3; stratigraphic details are available 1 ). Potential diachrony between the basin center and margin cannot be quantified with available data.…”
Section: Stratigraphic Contextmentioning
confidence: 99%